2009
DOI: 10.1007/s10295-009-0567-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of a sequential strategy of experimental design to optimize the inulinase production in a batch bioreactor

Abstract: A potential application of inulinase in the food industry is the production of fructoligosaccharides (FOS) by the transfructosilation of sucrose. The FOSs present many interesting functional properties besides their ability to increase the shelf-life and flavor of many products. The use of an industrial medium represents a good alternative to producing inulinase at low cost, since the activity may improve, or at least remain the same, as that obtained using a synthetic medium. This work was an optimization stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 19 publications
6
16
1
Order By: Relevance
“…These values are in agreement with previous work carried out by Mazutti et al (2007) and Treichel et al (2009), who evaluated the free enzyme in 0.1M sodium acetate buffer at pH 4.8. Mazutti et al (2007) found 17.2 U.mL -1 for v max and 7.1 mM for k m , while Treichel et al (2009) reported 10.7 U.mL -1 and 13.0 mM for v max and k m , respectively.…”
Section: Effect Of Ph On Inulinase Stabilitysupporting
confidence: 93%
See 3 more Smart Citations
“…These values are in agreement with previous work carried out by Mazutti et al (2007) and Treichel et al (2009), who evaluated the free enzyme in 0.1M sodium acetate buffer at pH 4.8. Mazutti et al (2007) found 17.2 U.mL -1 for v max and 7.1 mM for k m , while Treichel et al (2009) reported 10.7 U.mL -1 and 13.0 mM for v max and k m , respectively.…”
Section: Effect Of Ph On Inulinase Stabilitysupporting
confidence: 93%
“…Since Ed values represents the energy necessary to start the inactivation reaction and this value was lower for the immobilized enzyme than that for the free enzyme, one can conclude that the immobilized enzyme was less stable than the free enzyme when using this immobilization method (Santos et al, 2007). These results are similar to those reported by Mazutti et al (2007) (343.9 kJ.mol -1 ) and lower than those of Treichel et al (2009) (527 kJ.mol -1 ) for free inulinase.…”
Section: Effect Of Temperature On Inulinase Stabilitysupporting
confidence: 78%
See 2 more Smart Citations
“…Although high levels of inulinase production have been reported for Aspergillus niger (Poorna & Kulkarne, 1995;Singh & Gill, 2006;Mutanda, Wilheimi, & Whiteley, 2008;Dinarvand et al, 2012), yeasts of the genus Kluyveromyces have also attracted great interest. Besides being considered as GRAS (Generally Recognized as Safe), those yeasts have been described as some of the best producers of inulinase in several fermentative processes (submerged and solid fermentation) with a wide range of substrates (Selvakumar & Pandey, 1999;Silva-Santisteban & Maugeri, 2005;Xiong, Jinhua, & Dongsheng, 2007;Treichel, Mazutti, Maugeri, & Rodrigues, 2009;Neagu & Bahrim, 2011).…”
Section: Introductionmentioning
confidence: 99%